(untitled) (Research, Society and Development, 2020)
The sensory quality of the natural and peeled cherry coffee was subjected to drying at low temperature (40, 35 and 35 ºC) and cold (15 ºC), under low dew point temperature, using a prototype system drying and hygroscopic control, based on heat pump technology. For comparison, the sensory note of dry coffee was used at the property supplying the samples in a suspended and covered terrace (control). All samples submitted to laboratory drying showed better sensory quality in relation to dry coffee on the property. The best sensory score, 85, was obtained for natural coffee submitted to drying at 15 ºC, with a dew point temperature of 3.6 ºC and an average drying rate of 2.9 g kg-1 h-1.